Letter: diabetes mellitus increases the risk of hepatic encephalopathy in patients with cirrhosis—authors' reply. Issue 7 (9th September 2020) - Labenz, Christian; Wörns, Marcus‐Alexander
Abstract : LINKED CONTENT This article is linked to Labenz et al and Liu et al papers. To view these articles, visit https://doi.org/10.1111/apt.15915 and https://doi.org/10.1111/apt.16015